2019
DOI: 10.1136/bmjopen-2019-029851
|View full text |Cite
|
Sign up to set email alerts
|

Understanding patient profiles and characteristics of current chiropractic practice: a cross-sectional Ontario Chiropractic Observation and Analysis STudy (O-COAST)

Abstract: ObjectivesThere is no current detailed profile of people seeking chiropractic care in Canada. We describe the profiles of chiropractors’ practice and the reasons, nature of the care provided to their patients and extent of interprofessional collaborations in Ontario, Canada.DesignCross-sectional observational study.SettingPrimary care setting in Ontario, Canada.ParticipantsWe randomly recruited chiropractors from a list of registered chiropractors (n=3978) in active practice in 2015. Of the 135 randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…Of the 30% private sector spending, out-of-pocket spending accounts for about 15%, EHC plans about 12%, and others about 3% (CIHI 2019). In a recent study of Ontario chiropractors, they reported most patient encounters (68%) were paid out of pocket, with about 31% and 1% paid by EHC or work injury plans (Mior et al 2019).…”
Section: Insurance Coveragementioning
confidence: 99%
“…Of the 30% private sector spending, out-of-pocket spending accounts for about 15%, EHC plans about 12%, and others about 3% (CIHI 2019). In a recent study of Ontario chiropractors, they reported most patient encounters (68%) were paid out of pocket, with about 31% and 1% paid by EHC or work injury plans (Mior et al 2019).…”
Section: Insurance Coveragementioning
confidence: 99%
“…The treatment of children with spinal manipulative therapy (SMT) by chiropractors is controversial [1][2][3]. A recent study of Ontario chiropractors suggests that 5.5% of patients who consulted a chiropractor in the previous month are between the ages of 0 and 14 years [4]. A crosssectional survey of 140 chiropractors in Alberta indicates that all respondents treated children between 0 and 18 years of age and 13% of all visits in the previous month were with children [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is used to treat many musculoskeletal conditions, especially low back and neck pain [1]. Specifically for chiropractors, SMT is the most common treatment provided during a patient encounter [2][3][4]. It is estimated that the 12-month utilization rate for chiropractic services is 9.1% and a lifetime utilization of 22.2% worldwide [4].…”
Section: Introductionmentioning
confidence: 99%